The Influence of Self-Esteem, Social Support and Quarter Life Crisis in Early Adults - Wardha Hayati Khailia (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
When individuals enter the early adult stage, they are faced with many demands and challenges from those around them. Individuals who are unable to adapt to the various problems they face and are unable to progress to the expected stage of development will experience various psychological problems, such as quarter life crisis. The purpose of this study is to examine how much influence self-esteem and social support have on quarter life crisis in early adulthood. The participants of this study amounted to 106 male and female early adults in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. The approach used in this study is a quantitative approach. The sample determination used non-probability sampling technique, namely purposive sampling. The results of this study indicate that there is an influence between self-esteem and social support on quarter life crisis by 22.4%. This research self-esteem has a stronger influence than social support, because in the early adult phase it is able to make a meaningful contribution to the next process of individual life, as well as for healthy personal development.